A Literature Review of Clinical Studies Using Sa-am Acupuncture - Lim, Jinwoong; Kim, Yong-hwa; Kim, Yu-gon; Jeong, Hyeon-gyo; Shin, Kyung-moon; Shin, Dong-hoon; Jeong, Hwe-joon; Kang, Deok; Yang, Jae-woo; Oh, Ji-hoon; Yoon, Hong-ryoul; Jo, Jae-sung (Journal of acupuncture research, 2021)
Sa-am acupuncture originated in the Chosun Dynasty and is a distinct feature of Korean medicine. It has been used to treat various diseases and conditions in clinical practice however, there is insufficient scientific evidence to support the use of Sa-am acupuncture. We aimed to comprehensively review the clinical studies of Sa-am acupuncture retrieved from national and international databases (MEDLINE, EMBASE, the China National Knowledge Infrastructure, and 3 Korean databases). There were 52 articles reviewed including 29 case studies, 19 randomized controlled trials (RCTs), and 4 uncontrolled trials. Neurological disorders were the most frequently studied, and kidney tonification, and directional supplementation and draining were the most frequently used methods. Overall, the outcomes were generally positive however, there were many additional treatments together with Sa-am acupuncture reported in the case reports, and the quality of evidence was low in the RCTs. Future studies should report the detailed method of practicing Saam acupuncture treatment and focus on the specific effect of Sa-am acupuncture with rigorous design to scientifically support the clinical use of Sa-am acupuncture.